VR Setup to Assess Peripersonal Space Audio-Tactile 3D Boundaries - Lerner, France; Tahar, Guillaume; Bar, Alon; Koren, Ori; Flash, Tamar (Frontiers in Virtual Reality, 2021)
Many distinct spaces surround our bodies. Most schematically the key division is between Peripersonal Space (PPS), the close space surrounding our body, and an extrapersonal space, which is the space out of one’s reach. The PPS is considered as an action space, which allows us to interact with our environment by touching and grasping. In current scientific literature, PPS’ visual representations are appearing as mere bubbles of even dimensions wrapped around the body. Although more recent investigations of PPS’ upper body (trunk, head, hands), and lower body (legs, and foot) have provided new representations, no investigation has been made yet concerning the estimation of PPS overall representation in 3D. Previous findings have demonstrated how the relationship between tactile processing and the location of sound sources in space is modified along a spatial continuum. These findings suggest that similar methods can be used to localize the boundaries of the subjective individual representation of PPS. Hence, we designed a behavioral paradigm in virtual reality based on audio-tactile interactions, which has enabled us to infer a detailed individual 3D audio-tactile representation of the PPS. Considering that inadequate body-related multisensory integration processes can produce incoherent spatio-temporal perception, the development of a virtual reality setup and a method to estimate the representation of the subjective PPS volumetric boundaries will be a valuable addition for the comprehension of the mismatches occurring between body physical boundaries and body schema representations in 3D.